Study of Behaviour Adaptation of Dairy Cows after Regrouping and Facility Change - Miloslav Šoch; Jan Brouček; Michal Uhrinčať; Vladimír Tančin; Zuzana Palkovičová; Pavel Novák; Petr Zajíček; Milan Podsedníček (Scientific Papers Animal Science and Biotechnologies, 2023)
The objective of this study was to examine the influence of relocation dairy cows to different housing on some indicators of their maintenance behavior. Three days observation (72 hours) of 40 Holstein cows was done. The behaviour activities were registered at intervals of 10 minutes. The times of lying and ruminating showed steadily rising with each day (P<0.001). The time of standing was decreasing (P<0.001) from the first day to the third day after relocation. Period’s number differed also significantly in day’s comparison. Number of periods of total lying (7.34; 14.07; 16.34), and ruminating (14.32; 15.75; 18.58) were increasing (P<0.001). The converse trend (P<0.001) was showed in the variables of feeding (17.46; 12.73; 9.54) and total standing (24.93; 18.19; 12.41; P<0.001).